Do Macro-Economic and Technical Indicators Matter? - a Principal Component Analysis Approach for Equity Risk Premium Prediction (European Journal of Marketing and Economics, 2025)
Equity risk premium contains the property of reflecting the fundamental judgments of individuals regarding risk that might exists in the economic market and the price associated with that risk. For ERP forecasting, attention is also devoted to technical indicators apart from the macro-economic variables. A set of 14 technical and 14 macro-economic variables is selected for this purpose and based on a standard predictive regression framework; all forecasts are generated by regressing ERP on a constant and a lag of macro-economic or technical indicator. It is found that as compared to macro-economic variables technical indicators provide better indications about ERP estimates. By using National Bureau of Economic Research (NBER) data of business cycle expansion and recessions, relative strength of ERP predictability is also investigated and it is found more than twice for recessions as compare to expansions.
Keywords: Equity Risk Premium; Macro-economic Indicators; Technical Indicators; Forecasting.